P18.05.A Bevacizumab in atypical and anaplastic meningiomas: the BEMEN study. (5th September 2022) - Cerretti, G; Bosio, A; Maccari, M; Padovan, M; Caccese, M; Zagonel, V; Lombardi, G
Abstract: Background: meningiomas are the most frequent primary brain tumours. The current standard treatment for atypical and anaplastic meningioma can include surgical resection and radiotherapy. Despite the high rate of relapse no systemic treatment is indicated. Few data are available regarding the effectiveness of bevacizumab (BEV) in this setting. We performed a retrospective analysis investigating the efficacy and safety of BEV in meningioma patients relapsed after receiving surgery and radiotherapy. Gene mutations were also collected Material and Methods: we retrospectively analyzed patients treated with off-label BEV at the Veneto Institute of Oncology from July 2019 to February 2022. Major inclusion criteria were histologically-confirmed diagnosis of grade 2-3 meningioma (according to WHO 2016 classification), previous treatment with surgery and radiotherapy, no indication to further surgical reintervention or reirradiation, absence of major contraindications to the use of BEV. Data were estrapolated from local clinical records. Bevacizumab was administered at 10 or 5mg/Kg every 2 weeks (at physician's discretion) until progressive disease/death or unacceptable toxicity. Kaplan-Meier curves were used to estimate the survival rate; CTCAE v 5.0 was used to estimate treatment-related toxicities; RANO criteria were used for radiological assessment; NGS Foundation One panel was used to examine molecular data Results: the median follow up was 13 months (3-30 range). 26 patients were enrolled. Median age was 68 ys (29-84); male pts were 16 (61%); 61% (16 pts) with atypical meningioma, 38.5% (10 pts) with anaplastic meningioma; 27% (7 pts) had underwent 2 or more surgeries; 58% had had 2 or more RT treatments; 96.1% (25 pts) received <2 previous lines of systemic treatment. 77% (20 pts) and 23% (6) received BEV 10 and 5mg/Kg every 2 weeks, respectively. For 61% of patients (16 pts), NGS analyses were available; 62% (10 pts) harboured NF2 mutations (1 patient had a confirmed diagnosis of neurofibromatosis type 2), 23% (6 pts) CDKN2A/2B deletion, 11% (3 pts) PTEN mutation, 8% (2 pts) FGFR mutation, 8% (2 pts) JAK alteration. Overall survival (OS) rate was 82% and 62% at 6 and 12 months respectively; 6 months PFS rate was 83%. 4 patients showed PR, 11 SD, 6 PD, no patient had CR; 5 patients were not evaluable for response. Among evaluable patients the disease control rate (stability+response) was 71% and the objective response rate was 19%. Median PFS and OS were not reached19% (5 pts) experienced CTCAE grade 1 or 2 toxicity, mainly hypertension (4 pts); 1 patient experienced grade 3 hypertension. Conclusion: BEV showed very promising activity in recurrent grade 2-3 meningioma. The treatment was well tolerated. BEV should be considered an optimal therapeutic option in this setting of meningioma patients. The NGS results might be useful in identifying targetable mutations in case of further recurrence